Exclusive bed for thrombolysis. A simple measure that allows 85% of ischemic stroke patients to be treated in the first hour - Tansini, Gabriella; Ducci, Renata Dal-Prá; Nóvak, Edison Matos; Germiniani, Francisco Manoel Branco; Zétola, Viviane Flumignan; Lange, Marcos Christiano (Arquivos de Neuro-Psiquiatria, 2016)
The door-to-needle time is an important goal to reduce the time to treatment in intravenous thrombolysis. Objective Analyze if the inclusion of an exclusive thrombolytic bed reduces the door-to-needle time.Method One hundred and fifty patients admitted for neurological evaluation with ischemic stroke were separated in two groups: in the first, patients were admitted in the Emergency Room for intravenous thrombolysis (ER Group); in the second, patients were admitted in an exclusive thrombolytic bed in the general neurology ward (TB Group).Results Sixty-eight (86.0%) patients from TB Group were treated in the first 60 minutes of arrival as compared to 48 (67.6%) in the ER Group (p = 0.011).Conclusion The introduction of a thrombolytic bed in a general hospital setting can markedly reduce the door-to-needle time, allowing more than 85% of patients to be treated within the first hour of admission.
Keywords: neurology; stroke; treatment; thrombolytic therapy